Correlation Between Pursuit Score And Severity Of Coronary Artery Lesion Assessed by Syntax Score Among Non-ST-Segment Elevation Myocardial Infarction (NSTEMI) Patients in Adam Malik Hospital Medan - Indra, Ridho Kurnia; Ketaren, Andre Pasha; Putra, Hilfan Ade (CoinReads Media Prima, 2023)
Introduction: The PURSUIT score is a practical risk score for patients with acute coronary syndromes to assess prognosis and risk stratification. Prognosis and revascularization options in patients with multivessel disease can be determined based on the severity of coronary lesions based on angiography. However, only a few studies have investigated the association of this score with coronary lesion severity. This research is aim to evaluate correlation between PURSUIT score and severity of coronary artery lesions assessed by SYNTAX score in patients with NSTEMI at H.Adam Malik General Hospital Medan. Method: This research was a cross-sectional study in which the sample was taken by consecutive sampling at H. Adam Malik General Hospital in Medan on 70 patients diagnosed with NSTEMI. The hypothesis was evaluated using Pearson's correlation test for normally distributed numerical data or Spearman's correlation test for abnormally distributed data. The p value of 0.05 indicates statistical significance. Results: Mean PURSUIT score in this research was 11.0 + 3.31, while mean SYNTAX score was 25.6 + 10.8. A positive correlation was found between the PURSUIT score and the SYNTAX score with a low strength level (r = 0.258). Conclusion: The PURSUIT score has a weak correlation in predicting the complexity of coronary angiography among NSTEMI patients